The Secrets of Childhood, a Perspective to Montessori’s Theory of Early Childhood Education - Zidniyati, Zidniyati (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga Yogyakarta, 2016)
Maria Montessori founded a theory of education that has had a profound influence on the lives of thousands of children throughout the world since the beginning of the 20th Century. Her theory about education directed to implement the theory. The established of Casa dei bambini, a school in a slum area in Rome, was an important opportunity for her career that came in 1907, and it became an important starting point in her deep observation that leaded her to find lots of astonishing children’s secrets as well. Montessori’s theory of education was based on her conception of science, on her observation of children, and on her extensive research in anthropology, psychology, and pedagogy. To have a perspective of her ideas, it will be discussed in this writing about Montessori’s concept of a child as learner. That will lead us to have more comprehension of Montessori’s ideas of what she means of children’ secrets.